Prevalence, aetiology, and service mapping of dementia in rural Uganda. Part of DEPEND Uganda (Dementia Epidemiology, unmet Need and co-Developing Solutions in Uganda). [version 2; peer review: 2 approved] - Joseph Mugisha; Nicholas J Ashton; Claire J Steves; Racheal Alinaitwe; Josephine Prynn; Tunde Peto; Beatrice Kimono; Martin Prince (Wellcome Open Research)
Background Dementia prevalence in low- and middle-income countries is increasing, yet epidemiological data from African populations remain scarce. Crucial risk factors differ in Africa from more intensively studied global areas, including a higher burden of cerebrovascular disease and HIV, but lower rates of other risk factors like physical inactivity. Understanding dementia aetiology in African settings has been limited by the expensive and invasive nature of biomarker testing. This study leverages developments in blood-based and retinal imaging biomarker technology to examine the drivers of dementia in older Ugandans. People with dementia have complex needs benefiting from multi-dimensional support. Understanding current services will allow identification of barriers and opportunities to strengthen support available to people with dementia and their families. Methods The study is nested within the General Population Cohort run by the Medical Research Council/Uganda Virus Research Institute & London School of Hygiene and Tropical Medicine Research Unit. All adults aged 60+ (around 1400) are undergoing brief cognitive screening. In Part 1, cohort participants are selected based on screening scores to undergo detailed cognitive assessment, using methods developed by the 10/66 Dementia Research Group. Part 2 is a case control study of people with and without dementia using antecedent data, questionnaires, physical assessment, retinal imaging, and Alzheimer’s blood-based biomarkers. We will also compare disability, frailty, quality of life, and social engagement in people with and without dementia. Part 3 assesses current formal support structures for people with dementia through review of publicly available literature and expert interviews. Conclusions This is the first study in Africa using blood-based and retinal imaging biomarkers to examine pathological processes underlying dementia, and systematically map services available for people with dementia. This paves the way for effective policy strategies and further focused research regarding both dementia prevention and support for affected people and their families.